The Measurement of Information and Communication Technology Literacy: A Case Study of the Village Officials in Purbalingga - Retno Waluyo; Fergyanto E. Gunawan; Ito Setiawan (Bina Nusantara University, 2022)
The application of e-government for agencies from the basic level, sub-district, aims to create single-united data to be accessed from sub-district to district and even national. Then, human resources capability in Information and Communication Technology (ICT) literacy is also essential to maximize the application of e-government. However, the implementation of egovernment in Purbalingga has not been carried out optimally due to the lack of use of computers and the Internet by village officials. The research aims to measure the level of ICT literacy of village officials and the correlation between computer literacy and Internet literacy. The research is a quantitative study using a survey method with the People Capability Maturity Model (P-CMM) concept. Around 108 village officials in Purbalingga are involved in the research. The results show that ICT literacy is still at level 2. It implies that the village officials use computers and the Internet many times with the same usage pattern to assist their jobs. In addition, the correlation between computer literacy and Internet literacy is positive and strong. It means that if computer literacy increases, Internet literacy will also increase. Therefore, it is concluded that village officials in Purbalingga are accustomed to doing daily activities using computers and the Internet with the same usage pattern.